Does team diversity really matter? The connection between networks, access to financial resources, and performance in the context of university spin-offs - Petra Moog; Christian Soost (Small Business Economics, 2020)
University spin-offs (USOs) are an important driver for innovation, along with economic and social development. Hence, understanding which factors help them perform successfully is crucial, especially regarding their peculiarities in a scientific environment. This study focuses on essential factors such as team composition and diversity in USOs in the biotech sector in 64 founding teams in Switzerland and Germany. By identifying the team composition, and going beyond the usual team characteristics, along with checking in parallel for network and financing effects, the paper adds empirical evidence to the ongoing debate if and how team diversity in USOs affects the performance of this special group of newly founded firms. We test our hypotheses with the partial least squares method (PLS). Our results from the mediation model show how the diversity of teams is related to networks and financial resources and affects the performance. In addition, our study reveals the direct and indirect effects of team diversity on success in USOs. This way we contribute to the ongoing discussion on performance investigating the sources of team effects more in detail.
Keywords: L26; M13; L65; 330; Team composition; Team diversity; Entrepreneurship; Financing; Networks; Performance